Can epistemic belief predict the pedagogical belief of prospective elementary school teachers? - Saidah, Karimatus; Dardiri, Achmad; Fauziah, Pujiyanti (Intelektual Pustaka Media Utama, 2025)
It is important for prospective elementary school teachers to know their epistemic beliefs because this is related to beliefs about how to teach in schools and how learning should be done, which are called pedagogical beliefs. This study aims to investigate whether epistemic beliefs can predict the pedagogical beliefs of prospective elementary school students. This research method used a quantitative method with 179 elementary school teacher education students as research subjects. The data obtained were analyzed using a linear regression test. The results of this study indicate that students' epistemic beliefs can predict students' pedagogical beliefs, especially in terms of social studies learning concepts in elementary schools.